Integration of strengthening of character education and higher order thinking skills in history learning - Apriliana Rusly Haniah; Aman Aman; Risky Setiawan (Journal of Education and Learning (EduLearn), 2020)
The purpose of this study is to find integration packages for Strengthening Character Education (PPK) and Higher Order Thinking Skills (HOTS) in history learning at SMAN 1 Yogyakarta, which includes: (1) form of integration packaging for strengthening character education in history learning, (2) forms of integration packaging higher-order thinking skills in history learning, (3) constraints and solutions for integrating strengthening of character education and higher-order thinking skills in history learning.  This research is qualitative research with a naturalistic research type. The subjects in this study were the principal, deputy headmaster of the curriculum section, history teacher, and students who were drawn using purposive sampling techniques. The results showed: (1) Integration of character education reinforcement was found in history learning, namely in the planning, implementation and evaluation stages of learning. Forms of integration packaging or containers for strengthening character education that can be seen in learning activities and attitude assessments that contain religious values, conscientious, disciplined, responsible, communicative, collaborating, confident, caring, critical thinking, nationalist and creative; (2) The packaging for integrating higher-order thinking skills in history learning is found, namely in assessment and questions as well as in learning planning. The assessment carried out is an assessment of attitudes, knowledge, and skills that are integrated with the questions by conducting KD analysis. The results of the analysis then the teacher chooses the KD that can be made about HOTS;  and (3) Obstacles that are found that are technical in inserting character values in learning activities on historical subjects that are suggested to history teachers to always participate in the Subject Teachers' Deliberation (MGMP) which is felt by researchers to be very helpful for teachers to exchange information, and sharing about the obstacles encountered. For the constraints of making assessment instruments, advice to the Principal, Teachers, and Education Office to conduct socialization and training in making assessment instruments, the grid then starts making HOTS questions